Principles of Siddha Medicine - Miraaj, R.; Sailajah, S.; Laxsana, B. (Charithra malika kerala historical and educational cultural research museum Amaravila, Thiruvananthapuram, 2024)
The siddha medicine is the mother of traditional medical system of Tamil which came through the Dravidian culture in the period of the Indus valley civilization. The history of siddha medicine says that it was established by lord shive and this knowledge passed through Parvathy and the sage Agasthyar. Agasthyar described this knowledge to 18 Siddhars and they spread this knowledge to human beings by Kurulakavi. Sage Agasthyar is called as the father of Siddha Medicine. The main objective is to collect fundamental principles and philosophies of Siddha Medicine in various classical Siddha and Tamil literatures. Date for the review were collected from relevant Siddha text books and research sources from 11 th to 17 th December 2023. The physical structure of the universe and human are basically made up of five elements these are mann, neer, thee, kaatru, aakayam. The Siddha system contains three basic functional inits of the body Vatham, Pitham and Kapham, which are responsible for kinetic, metabolic and lubricating aspects of the body respectively in addition to that other 94 thathuvankal also formed from these which are the basic phenomenon and principle of Siddha system of Medicine, this is quoted by “Andathil ulathae pindam” by saddammunignanam. The philosophy of siddha medicine is Heavenly Bliss (Veedu peeru adaithal) and “prevention is better than cure” The preventive principles are explained elaborately in the text “ Theraiyar pini anugavithi ozhukkam”. Further scope in this regard can be carried out with the help of other ancient Tamil, Siddha literatures and traditional systems.
Keywords: Siddha medicine; Fundamental; Principles; Philosophy